Human Gastrointestinal Microbiota and Neural Activity: Effects of Probiotics on Mental and GI Health - Tomasi, David; Webb, Sophia (Jour Med Resh and Health Sci, 2020)
This review examines the general parameters of the microbiota-gut-brain axis, with special emphasis on a clinical-medical perspective and anthropological research foci. In particular, the authors focused on the observed vs. non-observed (observable) effects of psychobiotics on psychiatric conditions, as well as IBD and IBS comorbidities with psychiatric conditions; the latter was examined within the context of utilizing dietary changes to influence individuals’ microbiomes and to ameliorate GI and mental health. Despite some fascinating observations seen in preclinical animal models and promising outcomes observed in several clinical studies of probiotic supplementation on humans with psychiatric as well as GI conditions, this area of research warrants further scientific examination. This research is particularly important in order to provide scientific evidence supporting the use of probiotics (exclusively or as an adjunct treatment) for psychiatric and/or GI conditions in clinical settings. An important consideration in this sense is the need for standardized experimental methods, which can help guide evidence-based recommendations such as differences in dosing, timing, and duration of supplementation, as well as help elucidate genetic predispositions and potential dietary-pharmacological interactions. Such research methods would allow for a better understanding of the processes and mechanisms probiotics induce and/or cause within the context of human physiology.